2015
DOI: 10.1371/journal.pone.0129281
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hybrid Adaptive Controller for Manipulation in Complex Perturbation Environments

Abstract: In this paper we present a hybrid control scheme, combining the advantages of task-space and joint-space control. The controller is based on a human-like adaptive design, which minimises both control effort and tracking error. Our novel hybrid adaptive controller has been tested in extensive simulations, in a scenario where a Baxter robot manipulator is affected by external disturbances in the form of interaction with the environment and tool-like end-effector perturbations. The results demonstrated improved p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 32 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…In the first trial, the reference trajectory should be set to be periodic to satisfy the PE condition. From the second trial, for a better tracking performance, the reference point changes in a manner as in [52] as below , and it will be adapted iteratively. On the other hand, x d (t) is the reference trajectory used by the robot in practice.…”
Section: A Adaptation Of Reference Point and Feedforward Forcementioning
confidence: 99%
“…In the first trial, the reference trajectory should be set to be periodic to satisfy the PE condition. From the second trial, for a better tracking performance, the reference point changes in a manner as in [52] as below , and it will be adapted iteratively. On the other hand, x d (t) is the reference trajectory used by the robot in practice.…”
Section: A Adaptation Of Reference Point and Feedforward Forcementioning
confidence: 99%
“…The experiment shows the stability and the fast response to any action. Experiments have been conducted on manipulator controllers, where the fuzzy logic is used to control the joints of the robot (Smith et al (2015), McLauchlan et al (1997), Lea et al (1993) and Malki et al (1997)). …”
Section: Stereo Vision Based Object Tracking Control For a Movable Romentioning
confidence: 99%
“…A number of research results have shown that for any continuous smooth function ϕ(z) : Ω z → R over a compact set Ω z ⊂ R Nn [32], [33], we can apply RBFNN (9) to approximate ϕ(z). In particular, if N s is chosen a sufficiently large value, such that the ideal bounded weight W * exists, we have…”
Section: A Rbfnn Approximationmentioning
confidence: 99%